Atmospheric leach process of high-chromitite PGM-bearing oxidized mineralized ore through a single-stage and two-stage techniques - Mpinga, C.; Eksteen, Jacques; Aldrich, Chris; Dyer, Laurence (Elsevier, 2018)
© 2018 Elsevier Ltd The fast depletion of sulfide PGM-bearing minerals and the deteriorating socio-political environments in most primary PGM producing countries have triggered interest in exploring the recovery of these metals from high-chromium PGM-bearing oxidized ores – sometimes contain relatively high marketable PGM values – which have proven to be more difficult to process by conventional metallurgical practice which involves grinding, milling, froth flotation into a sulfide concentrate, smelting and matte production and chemical refining. This paper reports the results of an extensive evaluation campaign performed in both acidic sulfuric and chloride media. Leach tests were conducted in either a single-stage or a two-stage process and the results are compared and contrasted. Using a high-chromium PGM oxidized mineralized ore, the hybrid pyro-hydrometallurgical and low-temperature single-stage salt chlorination process proved successful for simultaneously and efficiently leaching Cu, Ni, Pt and Pd without the need and/or addition of further oxidizing agents. The technique is expected to be a direct treatment route from flotation concentrate to PGM refinery feed. Various chlorinating agents, including CaCl2, MgCl2, SnCl2and AlCl3, were tested. A CaCl2and MgCl2mixture acted synergistically for simultaneous dissolution of both Pt and Pd, achieving 99.7% Pt and 100% Pd recovery when thermally calcined at 650 °C, at a heating rate of 5.42 °C/minute for 6 h, and then leached at 90 °C for a minimum of 3 h in 6 M HCl. Copper and nickel extraction were lower but had not plateaued even after 24 h reaching 75.4 and 90.9% extraction respectively. It was also observed that when MgCl2was used on its own, it dissolves more platinum than palladium, while the opposite was true using CaCl2. The leaching process was controlled by surface chemical reactions with a determined activation energy of 46 kJ/mol. The dissolution rate was limited by the ratio of HCl volume-to-solid content. The recovery mechanism of Pt from PtAs2and some recommendations for future prospects have been suggested.